Conformational Switching of Pyrenes Associated on Hairpin Loop Region by DNA B‐Z Transition. Issue 29 (1st August 2022) - Nakamura, Mitsunobu; Yoshioka, Hibiki; Takada, Tadao
Abstract: DNA B−Z transitions play an important role in biological systems and have attracted much attention in DNA nanotechnology. DNA and its analogues have also been used as templates to construct helical chromophore associates with π‐interactions. We prepared DNAs with consecutive non‐nucleoside pyrene residues in the middle of d(CG) repeat sequences. The pyrene‐labelled DNAs adopted a unimolecular hairpin structure, in which the pyrenes associated in the loop region. They exhibited inversion of exciton‐coupled circular dichroism signals that can be ascribed to pyrene association through a DNA B−Z transition. This indicates that the conformation of pyrene associates can be switched from right to left by the DNA B−Z transition. The fluorescence of the pyrene‐labelled DNA changed when switching the association. Thus, pyrene‐labelled DNA can be utilized as a chiroptical molecular switch. Abstract : The pyrene‐labelled DNAs adopt a unimolecular hairpin structure, in which the pyrenes associated in the loop region. They exhibit inversion of exciton‐coupled circular dichroism signals that can be ascribed to pyrene association through a DNA B−Z transition. This indicates that the conformation of pyrene associates can be switched from right to left by the DNA B−Z transition.